Measuring Indigenous Well-Being: Psychometric Validation of the Pancawaluya Scale - Kulsum, Siti; Solehuddin, M; Yudha, Eka Sakti; Koswara, Dedi; Syakina, Bella; Zaelani, Abdul Qodir; Armanto, M Edi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2026)
Psychological well-being is understood differently across cultural contexts, yet many culturally grounded frameworks remain conceptually described rather than empirically tested. One such framework is Pancawaluya, a Sundanese indigenous model that defines well-being through five core values: Cageur (physical and mental health), Bageur (kindness and prosocial conduct), Bener (moral integrity), Pinter (knowledge and wisdom), and Singer (creativity and adaptability). Although these values are widely recognized in Sundanese philosophy and practice, their structure as a measurable psychological construct has not been systematically validated. This study examined the factor structure and internal consistency of the Pancawaluya Scale using Confirmatory Factor Analysis (CFA). Data were collected from 305 respondents and analyzed using LISREL. The results supported a five-factor model with satisfactory model fit indices (RMSEA = 0.031; CFI = 0.985; GFI = 0.958). Composite reliability indicated strong internal consistency, while AVE values suggested acceptable convergent validity for an indigenous construct in an early validation stage. The findings indicate that Pancawaluya can be operationalized as a coherent indigenous well-being construct. Its dimensions are theoretically discussed in relation to Islamic counseling principles, suggesting conceptual alignment in moral and spiritual values. This study provides an initial empirical foundation for future culturally grounded counseling research.